Strengthening Resilience through Risk Management in Islamic Microfinance Institutions: A Case Study of BPRS in Riau - Adiyes Putra; Khaidir, Widya; Nurnasrina; Siti Aisyah (Journal of Finance and Islamic Banking, 2025)
Purpose: This study aims to examine the implementation and effectiveness of risk management in Islamic Rural Banks (BPRS) in Riau Province, particularly in strengthening the resilience of sharia-compliant financing amidst growing financial uncertainties. Method: Using a qualitative case study approach, this research investigates two BPRS—Berkah Dana Fadhlillah and Hasanah—in both rural and urban contexts. Data were collected through interviews, observations, and document analysis involving practitioners, regulators, and academics. Results: The findings reveal that BPRS in Riau have implemented risk management systems in accordance with POJK No. 23/2019. Key strategies include policy formulation, development of risk-aware organizational culture, human resource enhancement, and financing segmentation—shifting from micro to consumer segments (e.g., murābaḥah). This strategic shift significantly reduced the Non-Performing Financing (NPF) rate. Implication: The research underscores the need for periodic updates in risk management strategies and enhanced professional capacity to maintain financing sustainability. Originality: This study contributes to the literature by integrating the concepts of organizational resilience and Islamic value frameworks in analyzing risk management practices at regional Islamic microfinance institutions.